Democratic Leadership as a Mediator Between Work Life Balance and Organizational Citizenship Behavior Among Millennial and Gen Z Employees in Indonesia's Beauty Industry - Pratama, Naziihah (Dinasti Publisher, 2025)
This study investigates the influence of Work Life Balance and Interpersonal Relationship on Organizational Citizenship Behavior (OCB), with Democratic Leadership serving as a mediating variable. The research was conducted at PT RANS Kosmetika Indonesia (SLAVINA), a startup in the beauty industry characterized by a predominantly Millennial and Generation Z workforce. Employing a quantitative research design and data analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM), the study demonstrates that both Work Life Balance and Interpersonal Relationship significantly impact OCB, both directly and indirectly via Democratic Leadership. The results yield theoretical implications for leadership and organizational behavior literature, while also offering practical insights for enhancing human resource strategies in dynamic and generationally diverse organizational settings.